Responsibilities of PT. GO-JEK Indonesia Semarang as Business Services Provider of Consumer Protection Online Services by Law Number 8 of 1999 Consumer Protection1999 CONSUMER PROTECTION - Annisa Rizqi Pradani (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2018)
PT. GO-JEK Indonesia utilizing the technology by issuing a GO-JEK application. People who will use the services-JEK Indonesia PT.GO application must download an app on a smartphone GO-JEK. The application, the customer is required to fill the data of identity. Charging the identity of the data, the driver will know the identity of the customer. Genesis ever happening to one of the customers PT.GO-JEK Indonesia Semarang is Ria (not her real name) use the services of GO-JEK driver got terror threat for comment after using the services of GO-JEK, of course is very detrimental to customers where the identity given to PT.GO-JEK Indonesia misused by the bad faith. This study aims to determine the responsibility of PT. GO-JEK Indonesia Semarang against losses incurred in terms of the confidentiality of customers' identities. This study uses a qualitative approach that is normative approach with the Act. Specifications spefikasi descriptive study clearly describe later with legal theory and practice of positive law linked to the research conducted. Responsibility PT.GO-JEK Indonesia Semarang to customers have been pursued by the Company by making the latest software in order to safeguard the identity of customers regarding compensation The Company provides compensation in accordance with the rules and regulations that have made the Company. Responsibility and compensation in accordance with the rules of Law No. 8 of 1999 on Consumer Protection.Keywords: Responsibility; Customer; PT.GO-JEK Indonesia